Serotyping and Seroprevalence of Mannheimia haemolytica, Pasteurella multocida, and Bibersteinia trehalosi and Assessment of Determinants of Ovine Pasteurellosis in West Amhara Sub-region, Ethiopia - Getnet, Kalkidan; Abera, Bezawit; Getie, Haymanot; Molla, Wassie; Mekonnen, Sefinew Alemu; Megistu, Bemrew Admassu; Abat, Anmaw Shite; Dejene, Haileyesus; Birhan, Mastewal; Ibrahim, Saddam Mohammed (Frontiers in Veterinary Science, 2022)
A cross-sectional study was undertaken in four (4) districts of West Amhara sub-region of Ethiopia with the aim of assessing the diversity and distribution of serotypes of Pasteurella species, their seroprevalence and associated risk factors, and knowledge, attitude, and practice of farmers towards ovine pasteurellosis. A total of 600 sheep sera were collected using multistage cluster sampling. Each sample was examined for the presence of six (6) serotype specific antibodies using indirect haemagglutination test. We are reporting a higher seroprevalence of 90.17% (541/600) in which all seropositive animals were shown to have been co-infected with multiple serotypes. Individual serotype prevalence showed that serotype A7 has the highest prevalence of 77.83% followed by A2 (74.33%), T15 (64%), T4 (62%), PA (60%), and A1 (39.17%). In this study, being female [OR: 2.45, 95% CI (1.09-5.52), p=0.031] and living in high altitude areas [OR: 20.29, 95% CI (2.54-161.95), p=0.004] were found to be significantly associated with sero-positivity. A questionnaire survey (n=384) employed in a face-to-face interview was used to assess knowledge, attitude, and practice of farmers related to ovine pasteurellosis. Accordingly, majority (72.4%) of respondents had inadequate knowledge level on the disease. Proportion of farmers with favorable attitude and good practices towards the disease was 50.26% and 77.6% respectively. This study is highly indicative that ovine pasteurellosis is a ubiquitous disease in the study area challenging the sheep production sector. The existence of diverse serotypes reported to lack cross-protective immunity is likely to explain why the current vaccination practice with the mono-serotype P. multocida biotype A vaccine is not providing adequate protection against outbreaks of the disease. Prioritization of one or more serotypes for inclusion in a multivalent vaccine should be dictated by the abundance and distribution of a particular serotype, its clinical importance, and its resultant economic impact. Furthermore, training of farmers on key aspects of the disease is vital in the implementation of effective disease management strategies through participatory approach. Data from the remaining regions of the country could help realize development of an effective vaccine that works best at national level.